The entrepreneurial option - Leiva-Aguilera, Javier (Anuario ThinkEPI, 2008)
In recent years, information managers have seen increased opportunities as a result of the evolution of technology. However, as time goes by we can see that many professionals continue to think that our options are limited to work in the public sector or, at most, in the private sector as employees. Nonetheless, the option of entrepreneurship is also a possibility.
Keywords: Work; Entrepreneurs; Company; Professional profile.